2017
DOI: 10.1093/annonc/mdx175
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive value of primary tumour side in patients with RAS wild-type metastatic colorectal cancer treated with chemotherapy and EGFR directed antibodies in six randomized trials

Abstract: This pooled analysis showed a worse prognosis for OS, PFS and ORR for patients with right-sided tumours compared with those with left-sided tumours in patients with RAS wt mCRC and a predictive effect of tumour side, with a greater effect of chemotherapy plus EGFR antibody therapy compared with chemotherapy or chemotherapy and bevacizumab, the effect being greatest in patients with left-sided tumours. These predictive results should be interpreted with caution due to the retrospective nature of the analysis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
574
5
19

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 714 publications
(630 citation statements)
references
References 50 publications
32
574
5
19
Order By: Relevance
“…The analysis by tumour location did not uncover a significant difference in os duration between treatments for either lcc or rcc (lcc hr: 0.96; 95% ci: 0.74 to 1.23; rcc hr: 1.14; 95% ci: 0.68 to 1.89). Similar results were observed for pfs 28 . Exclusion of patients with BRAFmutant tumours did not significantly affect those results.…”
Section: Second Linesupporting
confidence: 88%
See 3 more Smart Citations
“…The analysis by tumour location did not uncover a significant difference in os duration between treatments for either lcc or rcc (lcc hr: 0.96; 95% ci: 0.74 to 1.23; rcc hr: 1.14; 95% ci: 0.68 to 1.89). Similar results were observed for pfs 28 . Exclusion of patients with BRAFmutant tumours did not significantly affect those results.…”
Section: Second Linesupporting
confidence: 88%
“…In contrast to the differential benefits associated with egfr mAbs by sidedness for os duration, egfr mAbs appear to produce a superior orr in both lcc and rcc, as shown in the Holch et al 12 meta-analysis and the Arnold et al 28 pooled analysis. That observation could suggest that, if tumour shrinkage is the primary initial goal of treatment (for example, in patients with high-bulk, symptomatic, unresectable disease), an egfr mAb combined with chemotherapy might be more effective than bevacizumab combined with doublet chemotherapy.…”
Section: Tumour Responsementioning
confidence: 94%
See 2 more Smart Citations
“…24 , 25 Several studies also demonstrate the importance of taking PTL into account when evaluating treatment response, 26-28 and retrospective analyses from large phase III trials have demonstrated that patients with right-sided tumours have less benefit from the addition of EGFR-targeted therapy. 29 …”
Section: Discussionmentioning
confidence: 99%